Aqueous zinc ion battery electrolyte and aqueous zinc ion battery
By adding phosphate ester substances to the electrolyte of the aqueous zinc ion battery, modifying the interface structure of the negative electrode of the zinc negative electrode, the problems of zinc dendrites growth and side reactions were solved, and the cycle stability and capacity retention rate of the battery were significantly improved.
Patent Information
- Application Number
- CN202411813434.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-25
AI Technical Summary
The zinc metal anode of aqueous zinc ion batteries faces major challenges in the electroplating/peeling process during battery circulation, including the messy arrangement of zinc dendrites and poor hydrogen evolution reactions, resulting in poor circulation stability.
Phosphate ester substances are used as organic additives in the electrolyte, and by modifying the interface structure of the negative zinc electrode, the solvation structure is optimized, and dendrites are reduced.
It effectively inhibits the side reactions at the negative electrode interface of zinc, promotes the uniform deposition of zinc dendrites, and significantly improves the cycle stability and capacity retention rate of aqueous zinc ion batteries.
Smart Images

Figure CN119890479A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery, belonging to the field of batteries. Background Art
[0002] In recent years, with the rapid development of renewable energy and the urgent need for efficient energy storage solutions, it is particularly important to develop a low-cost, safe and reliable energy storage device. Among various battery devices, aqueous zinc-ion batteries (AZIBs) have attracted much attention due to their excellent safety, low cost and environmental protection characteristics. In addition, their negative electrode zinc metal has a high theoretical capacity (820mAh g -1 ) and low redox potential (-0.76 V compared to standard hydrogen electrode (SHE), and is considered to be the most promising candidate for large-scale energy storage devices.
[0003] However, the zinc metal anode of AZIBs faces major challenges in the electroplating / stripping process during battery cycling. When working at room temperature, zinc dendrites generated by the deintercalation reaction on the zinc anode surface of AZIBs are affected by the uneven electric field distribution at the interface between the electrolyte and the electrode, resulting in a disordered arrangement of the dendrites, making it easy for long and hard dendrites to pierce the diaphragm, thus causing the battery to short-circuit. In addition, the decomposition of active water molecules in the Zn2+ solvation structure can lead to undesirable hydrogen evolution reactions on the zinc anode surface, accompanied by the generation of by-products (such as basic zinc sulfate or basic zinc sulfonate) and corrosion of zinc metal. These problems have seriously restricted the industrial development of AZIBs. Summary of the invention
[0004] In view of the problems faced by aqueous zinc ion batteries, such as the growth of Zn negative electrode dendrites and side reactions (such as hydrogen evolution and zinc corrosion) caused by free water, the present invention provides an aqueous zinc ion battery electrolyte. The electrolyte can act as a modifier of the interface structure between the electrolyte and the zinc negative electrode through an organic additive phosphate, thereby optimizing the solvation structure, reducing the disordered dendrite growth of the zinc negative electrode and the side reactions caused by active water, so as to improve the cycle stability of AZIBs.
[0005] According to a first aspect of the present application, an aqueous zinc ion battery electrolyte is provided.
[0006] An aqueous zinc ion battery electrolyte comprises an organic additive, and the organic additive is a phosphate substance.
[0007] Optionally, the phosphate ester substance is selected from at least one of triethyl phosphate, trimethyl phosphate, dimethyl phosphate, diethyl phosphite, triethyl diphosphate, octyl phosphate, triaryl phosphate, and propylene diphosphate.
[0008] Phosphates are a class of ester compounds containing a phosphoric acid group, which are widely found in nature. Organophosphates are compounds containing an organic group bound to a phosphoric acid group (PO4). They have important applications in the chemical and industrial fields, especially in agriculture, plastics, coatings and medicine. The basic structure of this class of compounds consists of a phosphorus atom connected to four oxygen atoms, two of which are connected to the organic group through ester bonds (OC).
[0009] Phosphate will destroy Zn in solution 2+ The solvation structure can also be adsorbed on the surface of the zinc negative electrode to induce uniform deposition of zinc. This structure optimizes the Zn 2+ The desolvation of Zn 2+ Achieve more uniform deposition on the zinc negative electrode surface.
[0010] In some preferred embodiments of the present invention, the phosphate ester is triethyl phosphate, trimethyl phosphate and triethyl diphosphate; more preferably triethyl diphosphate. 2+ The close combination of the two leads to the outward orientation of the hydrophobic alkyl end of triethyl diphosphate, which effectively reduces the side reactions (such as hydrogen evolution and zinc corrosion) caused by the desolvated H2O on the electrode surface and optimizes the environment of the electrode surface.
[0011] Optionally, the electrolyte includes phosphate ester substances, zinc salt and water.
[0012] Optionally, the volume ratio of the phosphate substance to water is 1:200-1:10;
[0013] Preferably, the volume ratio of the phosphate substance to water is 1:100-1:25.
[0014] Optionally, the volume ratio of the phosphate substance to water is independently selected from any value of 1:200, 1:180, 1:160, 1:140, 1:120, 1:100, 1:90, 1:70, 1:50, 1:30, 1:10 or a range between any values.
[0015] Optionally, the molar concentration of the zinc salt is 0.1 mol / L-5 mol / L;
[0016] Preferably, the molar concentration of the zinc salt is 1.5 mol / L-2.5 mol / L.
[0017] Optionally, the molar concentration of the zinc salt is independently selected from any value in 0.1mol / L, 0.2mol / L, 0.5mol / L, 0.7mol / L, 1.0mol / L, 1.2mol / L, 1.5mol / L, 1.7mol / L, 2.0mol / L, 2.5mol / L, 3.0mol / L, 3.5mol / L, 4.0mol / L, 4.5mol / L, 5.0mol / L or a range value between any value.
[0018] Optionally, the zinc salt is selected from at least one of zinc sulfate, zinc chloride, zinc nitrate, zinc trifluoromethanesulfonate, zinc trifluoroformyl sulfonate, and zinc acetate.
[0019] Specifically, the zinc salt is selected from zinc trifluoromethanesulfonate.
[0020] Optionally, the electrolyte consists of phosphate ester substances, zinc salt and water.
[0021] Optionally, the method for preparing the electrolyte includes: mixing a phosphate substance and water to obtain a solution A, mixing a zinc salt and water to obtain a solution B, and adding solution A to solution B to obtain the electrolyte.
[0022] According to a second aspect of the present application, an aqueous zinc ion battery is provided.
[0023] An aqueous zinc ion battery, comprising a positive electrode, a negative electrode and an electrolyte;
[0024] The active material of the positive electrode is selected from at least one of vanadium-based materials, manganese-based materials, and Prussian blue compounds;
[0025] The negative electrode includes zinc;
[0026] The electrolyte is selected from the aqueous zinc ion battery electrolyte described above.
[0027] Optionally, the vanadium-based material is selected from at least one of sodium vanadate, potassium vanadate and vanadium pentoxide.
[0028] Optionally, the negative electrode is selected from at least one of zinc foil, zinc sheet, zinc foam, zinc powder and zinc rod.
[0029] The aqueous zinc ion battery comprises a positive electrode, a negative electrode and a diaphragm for separating the positive electrode and the negative electrode, and the cavity between the positive electrode and the negative electrode is filled with the electrolyte.
[0030] The modified electrolyte of the aqueous zinc ion battery provided by the invention has high specific capacity, good rate performance and cycle stability when used in the aqueous zinc ion battery.
[0031] The beneficial effects of this application include:
[0032] The application of phosphate substances as organic additives in aqueous zinc ion batteries provided in the present application, phosphate substances as AZIBs additives for interface structure modification, protect zinc negative electrode materials, inhibit side reactions at the zinc negative electrode interface and induce uniform deposition of zinc dendrites, and improve the cycle stability of zinc ion batteries. After adding phosphate substances to the electrolyte, the number of full battery cycles is as high as 4000, and the capacity retention rate is as high as 92%. It effectively improves the initial capacity and cycle stability of aqueous zinc ion batteries, has significant technological advancement, and good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The zinc-zinc symmetrical batteries prepared in Examples 1-3 and Comparative Example 1 were charged at 1 mA cm -2 Current density and 1mAh cm -2 SEM image of the zinc foil surface after 50 cycles of charge and discharge;
[0034] Figure 2 The full battery prepared in Example 4 was -1 Specific capacity at current density;
[0035] Figure 3 The full cell prepared in Example 5 was -1 Specific capacity at current density;
[0036] Figure 4 The zinc-zinc symmetric batteries prepared in Example 2 and Comparative Example 1 were subjected to different current densities (1, 1.5, 2, 2.5, 3 mA cm -2 ) and 1mAh cm -2 Charge and discharge rate performance at a fixed capacity;
[0037] Figure 5 The full cells prepared for Examples 1-3 and Comparative Example 1 were 1Ag -1 Discharge cycle performance at current density;
[0038] Figure 6 The full cells prepared in Example 2, Example 4, Example 5 and Comparative Example 1 were 1Ag -1 Discharge cycle performance at different current densities. DETAILED DESCRIPTION
[0039] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0040] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0041] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0042] Material:
[0043] Triethyl diphosphate, trimethyl phosphate, triethyl phosphate, vanadium pentoxide, and sodium hydroxide were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0044] Zinc trifluoromethanesulfonate and N-methylpyrrolidone were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0045] Anhydrous ethanol and conductive carbon black were purchased from Sinopharm Group.
[0046] Glass fiber diaphragms were purchased from Whatman of GE Healthcare Life Sciences.
[0047] Graphite paper comes from Langfang Hengtong Sealing Materials Co., Ltd.
[0048] The rest are commercially available.
[0049] All materials were used without further purification.
[0050] The morphology was characterized by scanning electron microscopy (SEM, SU8010).
[0051] Cyclic voltammetry (CV) tests were performed on the Princeton electrochemical workstation for cathode||Zn batteries with a scan rate of 0.1 mV s-1 and a voltage range of 0.2 to 1.6 V. The CV tests for Zn||Cu and Zn||Ti were performed in the voltage range of -0.3 V to 0.2 V with a scan rate of 0.1 mV s-1. -1 . The acquisition range of electrochemical impedance spectroscopy (EIS) was between 100000 Hz and 0.1 Hz. Constant current charge and discharge tests and constant current intermittent titration technique (GITT) tests were carried out on the Newar test system. In the three-electrode system, zinc foil was used as the working electrode (W), platinum wire as the counter electrode (C), and Ag / Ag Cl as the reference electrode (R), and linear sweep voltammetry (LSV) and linear polarization curve tests were carried out in different electrolytes. The scan rate was 2 mV s-1, and the scanning potential range was -1.25 to -0.75 V. All batteries were assembled under open air conditions and aged for 6 hours before electrochemical testing.
[0052] Example 1
[0053] Preparation of positive electrode material: 727.5 mg of V2O5 powder and 160 mg of NaOH were dissolved in 70 mL of deionized water and stirred evenly. The mixed solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 180 ° C for 24 h. After natural cooling, it was filtered, washed and vacuum freeze-dried to prepare sodium vanadate Na2V6O 16 Materials. Prepare Na2V6O 16 , conductive carbon black and polyvinylidene fluoride (PVDF) were mixed in NMP solvent at a mass ratio of 7:2:1. The slurry was milled in a planetary ball mill (YXQ2L 760W) for 3 hours (300 r min -1 ) ball mill. The graphite paper was cut into a circle of Φ = 14 mm, and the prepared slurry was evenly applied on the graphite paper and vacuum dried at 80 ° C for 12 h to remove NMP and obtain Na2V6O 16 Positive electrode, with a loading of about 2.5 mg cm -2 .
[0054] Preparation of negative electrode material: Use a slicer to cut pure zinc foil into 14mm diameter electrodes, immerse the electrodes in anhydrous ethanol solution for ultrasonic cleaning for 1-2 seconds. Lay the cleaned electrodes flat, dry them in a natural environment, and use them as negative electrodes for later use.
[0055] Preparation of electrolyte: Dissolve 2 mol / L zinc sulfonate in 10 mL deionized water at room temperature, stir and disperse for 24 hours to obtain a uniform clear solution, i.e., zinc sulfonate aqueous solution. Add triethyl diphosphate at a volume ratio of 1:100 to the above zinc sulfonate aqueous solution, stir and disperse for 24 hours to obtain triethyl diphosphate electrolyte.
[0056] Battery assembly: 1) Zinc-zinc symmetric battery: Use two identical zinc foils as positive and negative electrodes. Place a cut zinc foil in the positive electrode shell, put in a glass fiber diaphragm, use a pipette to drop 80μL of triethyl diphosphate electrolyte, and then place another zinc foil on top of the diaphragm. Put in a stainless steel gasket, then a spring, and finally buckle the negative electrode shell. Use a battery packaging machine to package the battery to obtain an electrolyte-modified aqueous zinc ion symmetric button battery, marked as Zn@Zn-Tp1 symmetric button battery. 2) Full battery: Use a piece of zinc foil as the negative electrode. Place a cut sodium vanadate positive electrode material in the positive electrode shell, put in a glass fiber diaphragm, use a pipette to drop 140μL of triethyl diphosphate electrolyte, and then place another piece of zinc foil negative electrode on top of the diaphragm. Then put in a stainless steel gasket, then the spring, and finally buckle the negative electrode shell. Use a battery packaging machine to package the battery to obtain an electrolyte-modified aqueous zinc ion button battery, marked as Zn@V-Tp1 button battery.
[0057] Example 2
[0058] The raw materials and preparation method are the same as those in Example 1, except that the volume ratio of the added triethyl diphosphate to deionized water is 1:50, the obtained zinc-zinc symmetric battery is marked as Zn@Zn-Tp2, and the aqueous zinc ion full battery is marked as Zn@V-Tp2.
[0059] Example 3
[0060] The raw materials and preparation method are the same as those in Example 1, except that the volume ratio of the added triethyl diphosphate to deionized water is 1:25, the obtained zinc-zinc symmetric battery is marked as Zn@Zn-Tp4, and the aqueous zinc ion full battery is marked as Zn@V-Tp4 button battery.
[0061] Example 4
[0062] The raw materials and preparation method are the same as those in Example 1, except that the additive of the electrolyte is triethyl phosphate, and the obtained aqueous zinc ion full battery is marked as Zn@V-TEP button battery.
[0063] Example 5
[0064] The raw materials and preparation method are the same as those in Example 1, except that the additive of the electrolyte is trimethyl phosphate, and the obtained aqueous zinc ion full battery is marked as Zn@V-TMP button battery.
[0065] Comparative Example 1
[0066] Preparation of negative electrode material: Use a slicer to cut pure zinc foil into 14mm diameter electrodes, immerse the electrodes in anhydrous ethanol solution for ultrasonic cleaning for 1-2 seconds. Lay the cleaned electrodes flat, dry them in a natural environment, and use them as negative electrodes for later use.
[0067] Preparation of zinc sulfonate electrolyte: Dissolve 2 mol / L zinc sulfonate in 10 mL of deionized water at room temperature, and stir and disperse for 24 hours to obtain a uniform clear solution, namely, a zinc sulfonate aqueous solution.
[0068] Battery assembly: 1) Zinc-zinc symmetric battery: Use two identical zinc foils as positive and negative electrodes. Place a cut zinc foil in the positive electrode shell, put in a glass fiber diaphragm, use a pipette to drop 80 μL of zinc sulfonate electrolyte, and then place another zinc foil on top of the diaphragm. Put in a stainless steel gasket, then a spring, and finally buckle the negative electrode shell. Use a battery packaging machine to package the battery to obtain an electrolyte-modified aqueous zinc ion symmetric button battery, marked as a Zn@Zn symmetric button battery. 2) Full battery: Use a piece of zinc foil as the negative electrode. Place a cut vanadium-based positive electrode material in the positive electrode shell, put in a glass fiber diaphragm, use a pipette to drop 140 μL of zinc sulfonate electrolyte, and then place another piece of zinc foil negative electrode on top of the diaphragm. Then put in a stainless steel gasket, then the spring, and finally buckle the negative electrode shell, and use a battery packaging machine to package the battery to obtain an electrolyte-modified aqueous zinc ion button battery, marked as a Zn@V button battery.
[0069] Performance testing and characterization:
[0070] The aqueous zinc ion symmetric button cells assembled with the electrolytes prepared in the above examples and comparative examples and the full cells composed of vanadium-based materials were used for morphological characterization and electrochemical performance testing using an electrolytic cell composed of a three-electrode method (working electrode: zinc sheet; reference electrode: silver chloride; counter electrode: platinum wire). The following performance tests and characterizations were all carried out at room temperature.
[0071] Figure 1 In the figure, (a) shows the appearance of the zinc foil of the zinc-zinc symmetric battery prepared in comparative example 1 after 50 cycles of charge and discharge; (b) shows the appearance of the zinc foil of the zinc-zinc symmetric battery prepared in example 1 after 50 cycles of charge and discharge; (c) shows the appearance of the zinc foil of the zinc-zinc symmetric battery prepared in example 2 after 50 cycles of charge and discharge; (d) shows the appearance of the zinc foil of the zinc-zinc symmetric battery prepared in example 3 after 50 cycles of charge and discharge. Figure 1 It can be seen that compared with the comparative example 1 without additive modification, the zinc foil in the embodiment 2 has a smoother appearance. This indicates that the zinc deposition in the embodiment grows laterally and is more uniform, which effectively inhibits the growth of zinc negative electrode dendrites.
[0072] Figure 2 The full battery prepared in Example 4 is 1Ag -1 The discharge capacity data is measured under the conditions. Figure 2 It can be found that the full battery of Example 4 experienced three short-circuit failures during the cycle, accompanied by capacity decay.
[0073] Figure 3 The full battery prepared in Example 5 is 1Ag -1 The discharge capacity data is measured under the conditions. Figure 3It can be found that the full battery of Example 5 had a short circuit failure problem during the cycle, and the capacity fluctuated in the later period.
[0074] Figure 4 The zinc-zinc symmetric batteries prepared in Example 2 and Comparative Example 1 were subjected to different current densities (1, 1.5, 2, 2.5, 3 mA cm -2 ) at 1 mAh cm -2 The charge and discharge rate data at a fixed capacity. Figure 4 It can be found that the polarization potential of the modified electrolyte in Example 2 is lower than the polarization potential of the unmodified electrolyte in Comparative Example 1, and Example 2 has better rate performance than Comparative Example 1.
[0075] Figure 5 The full cells prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were 1Ag -1 The discharge capacity data is measured under the conditions. Figure 5 It can be found that the full batteries of Example 1, Example 2 and Example 3 using the modified electrolyte have higher specific capacity retention rates, especially Example 2 has a specific capacity retention rate of less than 90% after 900 cycles. It can be seen that the capacity retention rate of this example has been improved, further verifying the modification effect of the phosphate additive.
[0076] Figure 6 The full cells prepared in Example 2, Example 4, Example 5 and Comparative Example 1 were 1Ag -1 The discharge capacity data is measured under the conditions. Figure 6 It can be found from the comparison that the performances of Example 2, Example 4 and Example 5 are much better than the relevant performances of Comparative Example 1, among which the comprehensive performance of Example 2 is the best.
[0077] By comparing Example 2, Example 4, Example 5 and Comparative Example 1, it can be proved that the phosphate additives do have a good inhibitory effect on the dendrite growth, hydrogen evolution corrosion, and the formation of by-products of the zinc negative electrode. The aqueous zinc ion battery obtained by adding the phosphate additive in the present application has a high specific capacity, good rate performance and cycle stability.
[0078] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An aqueous zinc ion battery electrolyte, characterized in that The electrolyte includes an organic additive, and the organic additive is a phosphate substance.
2. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that The phosphate ester substance is selected from at least one of triethyl phosphate, trimethyl phosphate, dimethyl phosphate, diethyl phosphite, triethyl diphosphate, octyl phosphate, triaryl phosphate, and propylene diphosphate.
3. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that The electrolyte includes phosphate ester substances, zinc salt and water.
4. The aqueous zinc ion battery electrolyte according to claim 3, characterized in that The volume ratio of phosphate esters to water is 1:200-1:10; Preferably, the volume ratio of the phosphate substance to water is 1:100-1:
25.
5. The aqueous zinc ion battery electrolyte according to claim 3, characterized in that The molar concentration of zinc salt is 0.1mol / L-5mol / L; Preferably, the molar concentration of the zinc salt is 1.5 mol / L-2.5 mol / L.
6. The aqueous zinc ion battery electrolyte according to claim 3, characterized in that: The zinc salt is selected from at least one of zinc sulfate, zinc chloride, zinc nitrate, zinc trifluoromethanesulfonate, zinc trifluoroformylsulfonate and zinc acetate.
7. The aqueous zinc ion battery electrolyte according to claim 3, characterized in that: The preparation method of the electrolyte comprises: mixing a phosphate substance and water to obtain a solution A, mixing a zinc salt and water to obtain a solution B, and adding the solution A to the solution B to obtain the electrolyte.
8. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte; The active material of the positive electrode is selected from at least one of vanadium-based materials, manganese-based materials, and Prussian blue compounds; The negative electrode includes zinc; The electrolyte is selected from the aqueous zinc ion battery electrolyte according to any one of claims 1 to 7.
9. The aqueous zinc ion battery according to claim 8, characterized in that: The vanadium-based material is selected from at least one of sodium vanadate, potassium vanadate and vanadium pentoxide.
10. The aqueous zinc ion battery according to claim 8, characterized in that: The negative electrode is selected from at least one of zinc foil, zinc sheet, zinc foam, zinc powder and zinc rod.
Citation Information
Cited By
Wide-temperature-range eutectic electrolyte for aluminum ion battery and application of wide-temperature-range eutectic electrolyte
CN120657280A
Aqueous zinc ion battery electrolyte and preparation and application thereof
CN121282388A